The potential of literary texts in integrative teaching from teachers’ perspective - Mirjana M. Stakić; Boško Lj. Milovanović (Inovacije u Nastavi)
Literary texts of different genres can be the starting point for intra-curricular and intercurricular connections. Our research, that included a sample of 225 primary school teachers, was conducted to establish the following: 1) how practitioners evaluate the potential of different types of literary texts as a starting point for integration in teaching and 2) what attitudes they have about how the application of a literary text as a starting point for integration affects the class organisation and dynamics. The obtained results show that teachers most positively evaluate the possibilities provided by prose literature as a starting point for integration, primarily the tales written by authors and folktales. When it comes to the class organisation and dynamics, the largest number of teachers agree (completely or mostly) on the following: all lower grades of primary school are suitable for using a literary text as a starting point for integration; the literary text can be used as a starting point for integration even beyond Serbian language classes; the application of the literary text as a starting point for integration affects the greater dynamics of teaching. A considerable number also agrees with the fact that in teaching practice the process of integration makes it difficult to choose an adequate literary text, but there are quite a few who are undecided when it comes to this issue. The obtained results show that primary school teachers positively evaluate the potential of literary texts as a starting point for integration in teaching, but they also raise the issue of an insufficient application in practice of this form of work and the need for additional support for practitioners in performing integration.